Low prevalence of infection by Sarcocystis neurona in horses from the State of Alagoas, Brazil - Fonseca de Araújo Valença, Sandra Regina (2019)
The aim of this study was to determine the prevalence of infection by Sarcocystis neurona in horses and identifypotential risk factors. Were analyzed 427 samples from 36 farms in 21 municipalities in the Alagoas State, Brazil. Presence of anti-S. neurona antibodies was diagnosed by indirect immunofluorescence antibody test (IFAT) and was confirmed using the immunoblot test. Risk factors were assessed through investigative questionnaires on animal management on the farms. The prevalence of anti-S.neurona antibodies was 2.8% (confidence interval, CI: 1.5-4.9%) from IFAT and 1.6% (CI:0.8-3.34%) from immunoblot, and there were positive horses on 16.6% of the studied farms. None of the variables studied presented associations with serological status for S. neurona. This is the first report on infection by S. neurona in horses reared in Alagoas, Brazil showing a low exposure to S. neurona in this region, but with significant numbers of foci.